Impact of the type of transcatheter heart valve on the incidence of early subclinical leaflet thrombosis. (22nd December 2017) - Ruile, Philipp; Minners, Jan; Schoechlin, Simon; Pache, Gregor; Hochholzer, Willibald; Blanke, Philipp; Jander, Nikolaus; Gick, Michael; Schröfel, Holger; Siepe, Matthias; Neumann, Franz-Josef; Hein, Manuel
Abstract: OBJECTIVES: The aim of this study was to investigate whether balloon-expandable and self-expandable transcatheter heart valves (THVs) differ in terms of the incidence of early subclinical leaflet thrombosis (LT). METHODS: Electrocardiographic-gated cardiac dual-source computed tomography angiography was performed at a median of 5 days after transcatheter aortic valve implantation and assessed for evidence of LT. RESULTS: Of the 629 consecutive patients, 538 (86%) received a balloon-expandable THV and 91 (14%) a self-expandable THV. LT was documented in 77 (14%) patients with a balloon-expandable valve and in 16 (18%) with a self-expandable valve ( P = 0.42). Similarly, LT was not significantly related to THV size ( P = 0.62). Corresponding to a lower rate of atrial fibrillation in the group with LT [25 (27%) vs 222 (41%), P = 0.01], anticoagulation at the time of computed tomography angiography was less frequent in this group [21 (23%) vs 183 (34%), P = 0.03]. Among the other potentially relevant covariables, there was no significant difference in the clinical baseline and the procedural characteristics between patients with and without LT (age 82 ± 6 years vs 82 ± 6 years, P = 0.51; ejection fraction 49 ± 10% vs 50 ± 10%, P = 0.47). In multivariate logistic regression analysis, including potentially relevant covariables, valve type was not significantly associated with LT ( P = 0.36). In the univariate and multivariate analyses, only the lack of anticoagulation at the time of computed tomography angiography was predictive of thrombus formation [0.563 (0.335–0.944), P = 0.03; 0.576 (0.343–0.970), P = 0.04]. CONCLUSIONS: In this large retrospective study of 629 patients, the type and the size of THV was not predictive of early LT.